Thin-Flap Laser In Situ Keratomileusis-Associated Dry Eye: A Comparative Study Between Femtosecond Laser and Mechanical Microkeratome–Assisted Laser In Situ Keratomileusis. Issue 1 (January 2022) - Abdel-Radi, Mahmoud; Abdelmotaal, Hazem; Anwar, Mohamed
Abstract : Objective: To assess and compare postlaser in situ keratomileusis (LASIK) dry eye after LASIK with planned thin flaps created by a femtosecond laser (FS) and mechanical microkeratome (MK). Methods: Patients were stratified according to the flap creation technique into FS and MK groups with planned 100 μm flap thickness in all eyes. Dry eye parameters including tear film break-up time (TBUT), Schirmer I test, ocular surface disease index (OSDI), and lower tear meniscus height and area (tear meniscus height [TMH] and tear meniscus area [TMA]) were assessed before surgery and at 3 and 6 months after surgery. Results: The study included 102 eyes of 55 patients (52 eyes underwent FS-LASIK/50 eyes underwent MK-LASIK). The preoperative characteristics including age, gender, and spherical equivalents were similar in both groups ( P >0.05). The difference in postoperative flap thickness was statistically significant ( P <0.05). In each group, dry eye parameters showed a statistically significant worsening ( P value<0.001) at 3 months with later significant improvement at 6 months but did not return to baseline. The mean TBUT, Schirmer I, and lower TMH and TMA were statistically higher, and the mean OSDI was statistically lower in FS-LASIK than the MK-LASIK group at both 3 and 6 months ( P value<0.001). The depth of ablation had a statistically significant correlation with Schirmer I at 6 months and OSDI at both 3 and 6 months post-LASIK ( P <0.05). Conclusion: The use of femtosecond laser technology in performing thin-Flap LASIK eye surgeries has improved the outcome of post-LASIK dry eye when compared with the mechanical microkeratome.